Is gentamicin administered to individual patients in optimal doses already at the beginning of therapy? - Göböová M.; Vaňo I.; Kissová V.; Fazekaš T.; Kuželová M. (Sciendo, 2019)
Introduction A gentamicin dose, which the physicians select, frequently does not take any pharmacokinetic parameters into consideration.